Tetralogy of Fallot with Absent Pulmonary Valve Syndrome: A Case Series - Hande İştar; Buğra Harmandar (Düzce Tıp Fakültesi Dergisi)
Tetralogy of Fallot (TOF) with absent pulmonary valve syndrome (APVS) is an extremely rare variant of TOF, with a ratio of 3-6%. Significant pulmonary insufficiency due to this valvular absence promotes dilation of the pulmonary arteries, and this can lead to airway compression during intrauterine life and after birth. The degree of compression is relative to the degree of hypoplasia of the respiratory tract. The severity of the respiratory problems indicates high mortality rates. This study aimed to present the short and mid-term outcomes following surgical repair of three TOF-APVS patients. One patient also had associated Townes-Brock Syndrome, which is extremely rare by itself. On follow-up, one patient could not be separated from cardiopulmonary bypass (CPB), and she was placed on arterio-venous extracorporeal membrane oxygenator (A-V ECMO) support before she died on the 5th day post-operatively. The patient with Townes-Brock syndrome died post-operatively 3.5th months due to pulmonary complications.